Kerangka kerja untuk pelaksanaan sistem pembuatan lean di perusahaan kecil dan sederhana (PKS) bagi komponen automotif - Ahmad Nasser, Mohd Rose (2015)
Global competition has driven automotive component manufacturing Small and Medium Industries (SMIs) to improve their business competitiveness and performance through implementing lean manufacturing system (LMS). However, the low success rate towards lean manufacturing implementation in many SMIs has given a serious course of concern. This research is aimed at formulating and developing a framework for lean manufacturing implementation in SMIs. This framework is particularly significant because it is set in a context of assisting the SMIs on how to systematically implement LMS and thus improves the rate of success. This study identifies the lean manufacturing critical success factors (CSFs) and LMS practices that are. key facets to success in LMS implementation. Further, in this research, 24 LMS practices were categorises into three categories of inter related LMS practices basic, intermediate and advanced. Then, the research investigates the effects of CSFs and categories of LMS practices on manufacturing performance. In this study, a mixed method research design was employed where the quantitative and qualitative data were collected sequentially. In the first phase, the survey questionnaire was sent to 250 automotive component manufacturing companies and the response rate was 24.8% from large companies and 14% from SMIs. The empirical analysis showed there were positive relationships between CSFs and LMS practices. The results also indicate that three groups of LMS practices contribute substantially to the manufacturing performance. There were six CSFs which are really important to the SMIs in order to be successful in LMS implementation, such as: leadership and commitment, training and education, effective communication, continuous improvement and customer management. Whereas, in the second phase, a multiple case study was performed in four SMIs and two big companies of Malaysian automotive components so as to further refine and understand the general scenario of LMS implementation in automotive component manufacturing SMIs. The cross-case comparison among the studied SMIs and big companies had discovered similarities on three CSF top management commitment and leadership, quality management and lastly on training and education. Apart from that, these companies also faced two main LMS implementation barriers such as: lack of lean manufacturing knowledge and workers quit their job. Finally, the compilation of quantitative and qualitative inputs were synthesised to develop a comprehensive framework for LMS implementation in SMIs. This framework was validated in one of the selected SMIs and proven that the suggested steps were applied accordingly. As a contribution to the community, this framework may contribute to the body of knowledge for both practitioners and academics in LMS implementation. In terms of theory, the framework has important strengths because it has explicitly framed the relationship between CSFs, LMS practices and manufacturing performance.